"Global counterinsurgency and the police-military continuum: introduction to the special issue". (4th July 2022) - Schrader, Stuart
Abstract: This introduction to the special issue "Global Counterinsurgency and the Police-Military Continuum" examines the emergence of global counterinsurgency in the twentieth century and introduces the critical concept of the police-military continuum. Through a review of the recent literature, it also provides a framework for analyzing the relationship of historical trends and contemporary developments in what is typically labeled "police militarization." It introduces and summarizes the fourteen original research articles in the special issue, which analyze United States, United Kingdom, Costa Rica, Haiti, India, Kenya, Malaysia, Tanganyika, and elsewhere. The introduction explains the genesis of the special issue in the aftermath of the rebellions of 2020, and it also considers new directions for research in the aftermath of the events of 6 January 2021 at the US Capitol, as well as what these events indicate about counterinsurgency's possible future mutations.